China's Public Diplomacy towards Africa: Strategies, Economic Linkages and Implications for Korea's Ambitions in Africa - Haggai Kennedy Ochieng (East Asian Economic Review (EAER), 2022)
Recent years have witnessed renewed interest in Africa and public diplomacy has emerged as the vital tool being used to cultivate these relations. China has been leading in pursuing stronger economic partnership with Africa while middle powers such as Korea are also intensifying engagement with the continent. While previous studies have analyzed the implications of China's activities in Africa on advanced powers, none has examined them from the paradigm of middle powers. This study fills this gap by assessing China's activities in Africa, their economic engagement and implications for Korea's interest in Africa. The analysis is qualitative based on secondary data from various sources and literature. The study shows that China's public diplomacy strategy involves a high degree of innovation and has evolved to encompass new tools and audiences. China has institutionalized a cooperative model that permeates many aspects of governance institutions in Africa, enabling it to strengthen their relations. This could also be helping China to adjust faster leadership transitions in Africa. Whereas the US is still the most influential country in Africa, China is influential in economic policies and has outstripped the US in infrastructure diplomacy. This could be because African policy makers align more with China's economic model than the US' mainstream economics. Chinese aid to Africa has been diversified to social sectors that are more responsive to the needs of Africa. Trade and investment relations between China and Africa have deepened, but so does trade imbalance since 2010. China mainly imports natural resources and raw materials from Africa. But this product portfolio is not different from Korea and the US. China's energetic insertion in Africa using various strategies has significant implications for countries with ambitions in Africa. Korea can achieve its ambitions in Africa by focusing resources in areas it can leverage its core strengths-such as education and vocational training, environmental policy and development cooperation.
Keywords: B22; B27; F21; 330; China; Africa; Public Diplomacy; Strategies; Economic Linkages; South Korea